Revolution and Exploration: the English Translations of Rousseau and Humboldt by Helen Maria Williams (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2017)
British author Helen Maria Williams (1759-1827) was a well-known figure in the eighteenth century literary circles, whose work was praised by Elizabeth Montagu, Samuel Johnson, Dorothy and William Wordsworth, Mary Wollstonecraft, Hester Piozzi or Alexander von Humboldt.  In her early poems  Edwin and Eltruda (1782), An Ode to the Peace (1783) and Peru (1784), Williams starts to reveal her political tendencies by appealing to strong empathic feelings as a key to social and political transformation. As a result of her interest in politics, she travelled to France in 1790 and published her most acclaimed work Letters from France (1790). However, the rest of her production has received little critical attention by modern scholars, who have overlooked her involvement in translation. Williams’ only extant novel, Julia (1790) is in fact a creative translation of Rousseau’s Julie ou La Nouvelle Héloïse (1761), in which Williams includes poems that evidence her interest in revolutionary politics. Four years later, she translated Bernardin de Saint Pierre’s Paul et Virginie, while she was imprisoned in Paris. While translating novels was regarded as a respectable exercise for women writers, Williams challenges gender assumptions by translating Researches (1814) and the seven volumes of Personal Narrative (1814-1829), which had been produced by one of the most influential eighteenth century scientists, Alexander von Humboldt. This article interrogates how Williams makes use of translation to access areas of knowledge traditionally restricted to men, such as philosophy, politics and science. For this purpose, I will focus on her translations of the work of two leading intellectual figures of the eighteenth century,  Rousseau and Von Humboldt.